Racial differences in neuromyelitis optica spectrum disorder - Kim, S; Mealy, M; Levy, M; Schmidt, F; Ruprecht, K; Paul, F; Ringelstein, M; Aktas, O; Hartung, H; Asgari, N; Tsz-Ching, J; Siritho, S; et al. (American Academy of Neurology, 2018)
OBJECTIVE:We aimed to evaluate racial differences in the clinical features of neuromyelitis optica spectrum disorder. METHODS:This retrospective review included 603 patients (304 Asian, 207 Caucasian, and 92 Afro-American/Afro-European), who were seropositive for anti-aquaporin-4 antibody, from 6 centers in Denmark, Germany, South Korea, United Kingdom, United States, and Thailand. RESULTS:Median disease duration at last follow-up was 8 years (range 0.3-38.4 years). Asian and Afro-American/Afro-European patients had a younger onset age than Caucasian patients (mean 36, 33, and 44 years, respectively; p < 0.001). During the disease course, Caucasian patients (23%) had a lower incidence of brain/brainstem involvement than Asian (42%) and Afro-American/Afro-European patients (38%) (p < 0.001). Severe attacks (visual acuity ≤0.1 in at least one eye or Expanded Disability Status Scale score ≥6.0 at nadir) at onset occurred more frequently in Afro-American/Afro-European (58%) than in Asian (46%) and Caucasian (38%) patients (p = 0.005). In the multivariable analysis, older age at onset, higher number of attacks before and after immunosuppressive treatment, but not race, were independent predictors of severe motor disabilities at last follow-up. CONCLUSION:A review of a large international cohort revealed that race affected the clinical phenotype, age at onset, and severity of attacks, but the overall outcome was most dependent on early and effective immunosuppressive treatment.